Estudio de factibilidad para el desarrollo de un sistema informático para llevar el control de vendedores con aplicaciones móviles para la Distribuidora de productos Lácteos J.R.R. de la ciudad de Babahoyo - Colins Guamanzara, Karen Ariana (2020)
The purpose of this research work is to demonstrate the way in which the company is directly affected by not having a system that allows control and monitoring of sales personnel to the dairy product distributor J.R.R. From the city of Babahoyo. During the development of this research work, the different problems and needs of the company were found. This project allowed to know more about the different information systems, mobile applications and geolocation that serve significantly to keep a corresponding control of the activities and routes of the sellers, as well as improve their work, also establish better satisfaction and communication with the client. In order to guarantee the effectiveness of the process.